Transport and land-use policies in Delhi - Geetam Tiwari (Bulletin of the World Health Organization, 2003)
Current transportation policies in mega-cities worldwide lead to major threats to health through traffic injuries, air pollution, noise, reduction in physical activities, and adverse impact on urban quality of life. In addition, a large section of the population in cities in low-income countries has to live in informal-sector, substandard housing. Many transportation policies fail to take enough account of their impacts on poverty and social exclusion, and they neglect the access and transportation demands of the more economically disadvantaged groups of society, who rely mostly on public transportation, walking, and cycling. Delhi, the capital city of India, is an interesting case because failure to consider the broad spectrum of health effects that may result from transport and land-use policies and investments has resulted in decisions that penalize the least affluent groups of the population and make it more difficult for them to get to jobs, education, health care, amenities, and services.